2015
DOI: 10.3390/ijerph120505310
|View full text |Cite
|
Sign up to set email alerts
|

Adult Psychotic Symptoms, Their Associated Risk Factors and Changes in Prevalence in Men and Women Over a Decade in a Poor Rural District of Kenya

Abstract: There have been no repeat surveys of psychotic symptoms in Kenya or indeed subSaharan Africa. A mental health epidemiological survey was therefore conducted in a demographic surveillance site of a Kenyan household population in 2013 to test the hypothesis that the prevalence of psychotic symptoms would be similar to that found in an earlier sample drawn from the same sample frame in 2004, using the same overall methodology and instruments. This 2013 study found that the prevalence of one or more psychotic symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Indeed only 29 % of those who are formally employed are women [ 69 ]. It is worth noting that we have also found a similar gender ratio in prevalence of psychotic symptoms in this sample in 2013, again with similar changes between 2004 and 2013 [ 70 ].…”
Section: Discussionsupporting
confidence: 67%
“…Indeed only 29 % of those who are formally employed are women [ 69 ]. It is worth noting that we have also found a similar gender ratio in prevalence of psychotic symptoms in this sample in 2013, again with similar changes between 2004 and 2013 [ 70 ].…”
Section: Discussionsupporting
confidence: 67%
“…The methods of the survey have been described in detail elsewhere [[4], [5], [6]]. The survey was conducted in Kisumu County, specifically in Maseno area .…”
Section: Methodsmentioning
confidence: 99%
“…Our prevalence rate of malaria [4], prevalence rates of mental disorders [[5], [6], [7], [8], [9], [10]], the influence of sociodemographic variables, and the association between malaria and mental disorders [11] have been previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled studies testing this alternative approach have shown sustained drinking reductions for many patients following behavioral treatments and pharmacotherapy 3,4 . With reduced drinking, long-term improvements have been reported regarding mortality rates, incidence of alcohol-associated injuries and accidents, levels of mood symptoms, quality of life, social functioning, along with significant weight reduction, a normalization of systolic and diastolic blood pressure, slowed progression of alcohol-attributable liver fibrosis, and recovery of ventricular heart function 5 .…”
mentioning
confidence: 99%